Chemical composition and biological activity of Nepeta cilicica - Iscan, Gökalp; Göger, Fatih; Demirci, Betül; Köse, Yavuz Bülent (Bangladesh Journal of Pharmacology, 2017)
In the present study, aerial parts of Nepeta cilicica were hydro-distilled for the essential oil. Furthermore, air-dried plant materials were extracted with methanol. According to GC-MS results, 35 compounds were characterized in the oil (totally 92%). Caryophyllene oxide, ?-caryophyllene and spathulenol (28.2, 8.9 and 4.2%) were found as main components of the oil. Sixteen compounds were detected by LC/MS, most of which were caffeoylquinic acid, luteolin and apigenin derivatives, in methanolic extract of the N. cilicica. Apart from DPPH radical scavenging activity, inhibitory effects on bacterial and yeast growth of essential oil and the methanolic extract were evaluated. Twenty-four different pathogenic bacterial and Candida strains were tested by M7-A7 and CLSI M27-A2 protocols respectively. The crude extract showed better inhibitory effects against bacteria strains than the essential oil. Both oil and the extract demonstrated strong inhibition on C. tropicalis at a concentration of 47.0 µg/mL (MIC). Video Clip of Methodology: CLSI microdilution broth method: 3 min 46 sec Full Screen Alternate